Pengaruh Pertumbuhan Ekonomi, Tingkat Pendidikan, dan Tingkat Pengangguran Terhadap Tingkat Kemiskinan di Kabupaten Jombang - Eka Rizki Kurniawan; Wiwin Priana Primandhana (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
From 2012 to 2023, researchers in Jombang Regency attempted to calculate the poverty rate and see how variables such as economic growth, education level, and unemployment rate affect poverty rate. This study used secondary data collected by BPS Jombang Regency. Multiple linear regression analysis is a major component of quantitative research methodology. So, considering all things, the data shows that poverty rate is significantly affected by economic growth, education level, and unemployment rate simultaneously. Various variables related to economic growth have a positive but insignificant impact on poverty, while education level has a negative but significant impact, and unemployment rate is positively and significantly related to poverty.